PENGEMBANGAN MEDIA POP-UP PELAJARAN SBDP MATERI KARYA SENI MEMBENTUK 3D DI SD NEGERI PEKAUMAN KULON 01 - Linda Maryana; Eka Titi Andaryani; Sri Sumartiningsih (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2024)
This study aims to: determine the feasibility of pop-up media in SBdP subjects in 3D art form material in SD Negeri Pekauman Kulon 01. This research is a type of research and development with the research subjects of grade IV SD Negeri Pekauman Kulon 01. This research was conducted with a 4D model which consisted of (1) the Define stage and carried out a needs analysis, curriculum, assignments and concepts. (2) The design stage is carried out by collecting references, collecting drafts, compiling materials, and layouts. (3) The develop stage is carried out by making the product design into a product and validating the product repeatedly until a valid product is produced and tested with individual trials, small groups and large groups. (4) The disseminate stage is carried out by distributing the product to the class being tested. Based on the research results, pop-up media is suitable for use in learning three dimensional art work material from the validation results of expert lecturers of 3.31, including the feasible category and elementary school teachers of 3,785 in the category very suitable for use in learning. After the validity test was carried out with validation, it was then tested on students. Individual trials got a percentage of 96.59% with a learning implementation of 99.4%, small group trials got a response of 97.73% with a result of implementation of learning 99.35% and large group trials got a percentage of students' responses of 96.30% with learning implementation of 98.1%.